Continuation of the Andijan Main Traditions - Temirov Murodjon Anvarovich; Abdujalilov Abduvohid Abdujamilovich; Ruziev Nuriddin Mukhamadalievich (International Journal on Orange Technologies, 2021)
It was noted that one of the most important tasks is to get acquainted with the meaning of the Andijan pottery traditions, their compositional solutions in color and shape, the physiological and psychological strength of pottery traditions. The history of the Andijan pottery traditions, their connection with other pottery schools, scientific research, the study of pottery.The study of the theory of selected colors and psyche in the art of Andijan ceramics was taken as an object.